Una nueva especie de pez del género Bryconamericus (Ostariophysi: Characidae) del río Magdalena, con una clave para las especies de Colombia - Roman Valencia, César; A. Vanegas Ríos, James; I. Ruiz C., Raquel (Revista de Biología Tropical, 2008)
Based on a series of 90 specimens, and using morpho-metric, meristic and osteological characters, a new species of the genus Bryconamericus is described from Pontesuela Creek at the mouth of Coclina Creek in the middle Magdalena river Basin of Colombia. We use box graphs with 99% confidence intervals to illustrate the extent of meristic character overlap and to help distinguish this new taxon from other species of the Magdalena River. The species can be distinguished from all congeners by the combination of the following characters: the higher number of lateral line scales (50-54 vs. 30-50, except B. terrabensis with 47-54); more scales between the lateral line and the dorsal fin origin (9-11 vs. 4-9); more scales between the lateral line and the pelvic fin origin (8-10 vs. 2-8); more scales between lateral line and anal fin origin (8-10 vs. 2-8, except B. terrabensis with 6-9) and more predorsal scales (16-18 vs. 9-16, except B. huilae with 14-19 scales, B. galvisi with 12-17 and B. tolimae with 13-17).